2006
DOI: 10.1038/nmeth974
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive protein detection via triple-binder proximity ligation assays

Abstract: The detection of weakly expressed proteins and protein complexes in biological samples represents a fundamental challenge. We have developed a new proximity-ligation strategy named 3PLA that uses three recognition events for the highly specific and sensitive detection of as little as a hundred molecules of the vascular endothelial growth factor (VEGF), the biomarkers troponin I, and prostate-specific antigen (PSA) alone or in complex with an inhibitor--demonstrating the versatility of 3PLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 13 publications
2
100
1
3
Order By: Relevance
“…We have previously demonstrated that the proximity ligation mechanism can be extended to using sets of three antibodies (9,20). This could provide unique opportunities to investigate constellations of several phosphorylations or other PTMs in individual protein molecules, something that would present great difficulties using methods like mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the proximity ligation mechanism can be extended to using sets of three antibodies (9,20). This could provide unique opportunities to investigate constellations of several phosphorylations or other PTMs in individual protein molecules, something that would present great difficulties using methods like mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…In asymmetric PLA, connector oligonucleotide binding affinity towards the probe strands is weakened in one end, reducing the probability of target-independent ligation (29). Triple-specific proximity ligation assay (3PLA) lowers background signal by using weakly hybridizing oligonucleotides to temporarily block unbound probes and increases specificity through triple recognition of three separate target probes (30). Landegren et al reported a 100-fold increase in sensitivity compared to standard homogenous PLA when assaying recombinant VEGF (22).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…PDGF-BB was measured in lysates and medium from four plates for each genotype. Measurements were done in triplicate using triple proximity ligation assay as described (Schallmeiner et al 2007). …”
Section: Pdgf-bb Proximity Ligation Assaymentioning
confidence: 99%